2016
DOI: 10.1093/intqhc/mzw025
|View full text |Cite
|
Sign up to set email alerts
|

SIMulation of Medication Error induced by Clinical Trial drug labeling: the SIMME-CT study

Abstract: SIMME-CT is the first simulation-based learning tool to focus on investigational drug labels as a risk factor for medication error. SIMME-CT was also used as a training tool for staff involved in clinical research, to develop medication error risk awareness and to validate competence in continuing medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…The twelve articles did not demonstrate the inclusion of patients, they involved the development of some teaching resource or creation of resources to reduce and prevent adverse drug events through simulation methods. Of these articles, 01 involved the creation of a freeze-dried ampoule of Dantrolene (Giraldo-Gutiérrez et al, 2018); 01 identified unreported errors (You et al, 2015); 02 studies developed drug labels for simulations (Dollinger et al, 2016;GARCIA, et al, 2017); 01 alert created in simulations, 2017); 01 created alerts in medication prescription software to avoid errors (RUSS et al, 2014); 01 used simulated software to verify medication orders and reconciliation by pharmacists (Metzger et al, 2015); 01 involved creating software to train on security vulnerabilities in chemotherapy orders (Wyatt et al, 2020); 01 created a gamification simulator for preparing medicines (Booth et al, 2018); 01 creation of a device for the infusion of intravenous medications after checking the barcode (Khan et al, 2016); an integrative review that shows that high and low fidelity simulations contribute to knowledge acquisition (Santana et al, 2020); one study compared the frequency of errors after safety simulation training (JONES et al, 2021); one developed a simulated electronic medication administration system (Booth et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The twelve articles did not demonstrate the inclusion of patients, they involved the development of some teaching resource or creation of resources to reduce and prevent adverse drug events through simulation methods. Of these articles, 01 involved the creation of a freeze-dried ampoule of Dantrolene (Giraldo-Gutiérrez et al, 2018); 01 identified unreported errors (You et al, 2015); 02 studies developed drug labels for simulations (Dollinger et al, 2016;GARCIA, et al, 2017); 01 alert created in simulations, 2017); 01 created alerts in medication prescription software to avoid errors (RUSS et al, 2014); 01 used simulated software to verify medication orders and reconciliation by pharmacists (Metzger et al, 2015); 01 involved creating software to train on security vulnerabilities in chemotherapy orders (Wyatt et al, 2020); 01 created a gamification simulator for preparing medicines (Booth et al, 2018); 01 creation of a device for the infusion of intravenous medications after checking the barcode (Khan et al, 2016); an integrative review that shows that high and low fidelity simulations contribute to knowledge acquisition (Santana et al, 2020); one study compared the frequency of errors after safety simulation training (JONES et al, 2021); one developed a simulated electronic medication administration system (Booth et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…IMP container labels are often printed in small fonts that are difficult to read. Aside from the strict regulatory aspects of labeling, information that is readable, useful, understandable, and in the patient’s own language should be placed on container labels in order to encourage the patients to read them, and in order to reduce medication errors [1721]. As reported in other studies, pictograms on container labels could be useful [22].…”
Section: Discussionmentioning
confidence: 99%
“…They related mostly to dosage identification, trial code identification, drug confusion and expiry date. 18 Most errors were made with products that they characterized as ''high risk labels,'' according to their score of the risk of error with label information and the risk of confusion with another study. Considering that studies may involve high-risk drugs, appropriate warnings and precautions should also be highlighted on labels for these products in addition to the eight required elements.…”
Section: Conformity and Variabilitymentioning
confidence: 99%